2003
DOI: 10.1002/pi.1410
|View full text |Cite
|
Sign up to set email alerts
|

The effect of morphology on the optical properties of transparent epoxy/montmorillonite composites

Abstract: Three kinds of epoxy-based transparent nanocomposites were prepared by the reaction of alkylammonium-exchanged montmorillonite (AMT) with diglycidyl ether of bisphenol A (DGEBA) and triethylamine as the curing agent. The morphology of these composites was characterized by X-ray diffraction, scanning electron microscopy and transmission electron microscopy. The effect of morphology on the optical transparency of epoxy/AMT composites (Ep/AMT) was investigated. The light transmittance of Ep/AMT depended greatly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…In general, several factors including the matrix properties, the interfacial refractive index difference between matrix and dispersed organic/inorganic domains, and the size of the dispersed organic/inorganic domains govern the optical properties of polymer composites [29,30]. Figure 4 shows the optical transmittance of the prepared chitosan and (nano) Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…In general, several factors including the matrix properties, the interfacial refractive index difference between matrix and dispersed organic/inorganic domains, and the size of the dispersed organic/inorganic domains govern the optical properties of polymer composites [29,30]. Figure 4 shows the optical transmittance of the prepared chitosan and (nano) Fig.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The measurement of the transmission percentage at 550 nm reveals that all substrates are transparent with around 87 % for the neat PLA that show the highest transmittance, around 75% transmittance for the PLA/CL30B/EBS-ELPPF samples and around 73% transmittance for just PLA/CL30B/EBS substrate ( Table 4). The literature allows linking the transparency to higher exfoliation degree of clays [51][52][53]. Indeed, the nanocomposites could be more transparent due to the changes of the particle size and spacing.…”
Section: Citationmentioning
confidence: 99%
“…Salahuddin et al [34] reported that a transparent epoxy/clay nanocomposite could be achieved using an organically modified montmorillonite (OMMT). Deng et al [35] investigated the effect of morphology on the optical transparency of epoxy/organomodified montmorillonite composites. The light transmittance of nanocomposites depended greatly on the exfoliation degree of organoclay in the epoxy matrix, and the transmittance of the composites with higher exfoliation degree was notably higher than that with lower exfoliation degree under the same organoclay content.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of physical properties of polymers, optical absorption spectrum is one of the most important tool for understanding band structure, electronic properties, and optical constants (refractive and absorption indices) of pure and composite polymers [30]. Recently, some authors have investigated the some optical properties of polymer/clay nanocomposites [31][32][33][34][35]. In particular, these studies focus on the determination of optical transparency of nanocomposites by loading organoclay.…”
Section: Introductionmentioning
confidence: 99%